Unlocking collective cooperation in the midst of COVID‐19: The role of social support in predicting the social class disparity in cooperation. (20th December 2021) - Tanjitpiyanond, Porntida; Álvarez, Belén; Jetten, Jolanda; Bentley, Sarah V.; Casara, Bruno Gabriel Salvador; Crimston, Charlie R.; Ionescu, Octavia; Jarukasemthawee, Somboon; Krug, Henning; Selvanathan, Hema Preya; Steffens, Niklas K.; Wang, Zhechen; et al.
Abstract: We examined whether (the lack of) social support can explain why researchers have found lower rates of adherence to follow public health guidelines amongst people who perceived themselves as coming from lower social class backgrounds during the COVID‐19 pandemic. To do this, we surveyed 5818 participants from 10 countries during the first wave of lock‐down. Contrary to previous findings, social class was not related to general adherence to COVID‐19 regulations or desire to engage in citizenship behaviours (e.g., showing initiatives to help others during the pandemic). However, we found evidence of an indirect effect whereby those who perceived themselves as higher social class were more likely to be both the recipient and provider of social support which in turn predicted greater adherence and desire to engage in citizenship behaviours during the earlier wave of the pandemic. Our findings highlight the importance of social support in unlocking potential for collective cooperation (i.e., adherence to COVID‐19 rules and desire to engage in citizenship behaviours ). They suggest that instead of enforcing strict regulations, government authorities need to address existing social support barriers within lower income communities to facilitate cooperation from everyone in the community.